Confirming Secured E-Commerce Transaction Environment Supported by A New Symmetric Key Cryptographic Scheme - Biswas, B; Khan, A.K (International Journal of Computer Sciences and Engineering, 2025)
With the advances of the internet technology, people are more relying on the e-commerce transaction. However, due to security paucities, it is often subjected to many controversies. There are different existing cryptographic techniques to provide security for the transactions in e-commerce. Nevertheless, the enhancement in technology causes different attacks on the conventional cryptographic schemes, which resulted many security threats to the transactions. A new symmetric key cryptographic algorithm for e-commerce transaction has been proposed in this paper which can provide better security for the transactions over the internet. The new randomized key generation, substitution box generation and permutation box generation algorithms have been proposed for this cryptographic technique. This proposed algorithm has been proved as the cryptographic process with randomness as its avalanche effect is more than 50%. Additionally, correlation coefficient of this method is also better than the original AES. Moreover, the encryption and decryption time of this proposed algorithm is much less than the original AES. So, this proposed algorithm would ensure better security to the e-commerce transaction with less time to make the transaction more efficient